The Level of Expression of the Minor Pilin Subunit, CooD, Determines the Number of CS1 Pili Assembled on the Cell Surface of Escherichia coli - Sakellaris, Harry (American Society for Microbiology, 1999)
CooD, the minor subunit of CS1 pili of enterotoxigenic Escherichia coli, is essential for the assembly of stable, functional pili. We previously proposed that CooD is a rate-limiting initiator of CS1 pilus assembly and predicted that the level of CooD expression should therefore determine the number of CS1 pili assembled on the cell surface. In this study, we confirm that CooD is required for the initiation of pilus assembly rather than for the stabilization of pili after they are assembled by demonstrating that specific modulation of cooD expression also modulates the number of CS1 pili on bacterial cells.